(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2026)
This study presents the results of mathematical modeling of hydrogeological processes in intensively irrigated areas using the Malik experimental site as a case study. The investigated area is characterized by a four-layer hydrogeological structure consisting of cover sandy loams and loams, gravel-bearing sand deposits, low-permeable loam layers, and underlying sandy aquifers. A pumping test conducted at well 2ts and observation wells was used to evaluate the hydrogeological parameters of the aquifer system. Preliminary hydraulic conductivity coefficients were determined using the AquiferTest software package, followed by calibration of a numerical groundwater flow model. During the modeling process, calculated groundwater levels were compared with observed data, and filtration parameters together with storage coefficients were adjusted to minimize discrepancies between measured and simulated groundwater heads. The calibrated hydraulic conductivity values were determined as 0.03 m/day for cover loams, 5 m/day for gravelly sands, 0.02 m/day for dense loams, and 14 m/day for fine-grained sands. The results showed that irrigation infiltration and collector-drainage systems significantly influence groundwater regime formation in intensively irrigated areas. The developed mathematical model can be used for groundwater regime prediction and assessment of meliorative conditions in irrigated lands.